PERBANDINGAN EFEKTIVITAS MULTIMEDIA PEMBELAJARAN INTERAKTIF DAN MEDIA PRESENTASI TERHADAP HASIL BELAJAR GEOGRAFI SISWA SMA - Rahmad Suryadi; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to compare the effectiveness of the use of interactive learning multimedia and presentation media on the learning outcomes of Geography of Senior High School students. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The subjects of the study were students of grade XI Phase F of SMA Negeri 1 Batipuh consisting of two classes, namely the experimental class using interactive learning multimedia and the control class using conventional presentation media. The research instrument was a multiple-choice objective test that had been tested for validity, reliability, difficulty level, and discrimination power. Learning outcome data were analyzed using a t-test. The results showed that the average learning outcome of students in the experimental class was 80.16, while the control class was 75.94. The results of the hypothesis test showed a t-value of 2.247 greater than the t-table of 1.999 at a significance level of 0.05. Thus, it can be concluded that interactive learning multimedia is more effective than presentation media in improving the learning outcomes of Senior High School students in Geography.